WORKSHOP KURIKULUM MERDEKA BELAJAR DI YAYASAN SPMAA BALI, DESA PEMECUTAN KELOD, DENPASAR BARAT - Ida Ayu Made Wedasuwari; Dewa Gede Bambang Erawan; I Nyoman Suparasa; Satria Faithfull Muttani Miraj Muchtar (Bajang Institute, 2022)
The curriculum is the soul of education that must be evaluated innovatively, dynamically, and periodically adapted to the times and science and technology, competencies needed by the community and graduate users. In this regard, in an effort to restore learning caused by the pandemic, the Ministry of Education and Culture issued a policy in the development of the Independent Curriculum. The Independent Learning Curriculum is the development and implementation of an emergency curriculum launched to respond to the impact of the Covid-19 pandemic. Based on observations made to teachers at the SPMAA Bali Foundation, they still do not understand the Independent Learning Curriculum, this is what causes the service team to do community service at the SPMAA Bali Foundation. This activity is a workshop activity to provide understanding and assistance on the implementation of the independent learning curriculum, preparation of lesson plans and also the preparation of learning media. The results of this service indicate that the effectiveness of the independent learning curriculum workshop is 94.5%, which means that this activity is very good for increasing teacher knowledge about the independent learning curriculum.